Inositol 1,4,5-trisphosphate receptor type 1 autoantibody (ITPR1-IgG/anti-Sj)-associated autoimmune cerebellar ataxia, encephalitis and peripheral neuropathy: review of the literature - Jarius, Sven; Bräuninger, Stefan; Chung, Ha-Yeun; Geis, Christian; Haas, Jürgen; Komorowski, Lars; Wildemann, Brigitte; Roth, Christian (Journal of neuroinflammation, 2022)
In 2014, we first described novel autoantibodies to the inositol 1,4,5-trisphosphate receptor type 1 (ITPR1-IgG/anti-Sj) in patients with autoimmune cerebellar ataxia (ACA) in this journal. Here, we provide a review of the available literature on ITPR1-IgG/anti-Sj, covering clinical and paraclinical presentation, tumour association, serological findings, and immunopathogenesis.
Gesehen am 19.08.2022